Development of Powtoon-Based Mathematics Learning Media on Set Materials - Devi Apriliani, Sri (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2022)
Learning media is everything in the form of physical and technical in the learning process that can assist teachers in making it easier to convey subject matter to students so as to facilitate the achievement of learning objectives that have been formulated by the teacher. The purpose of this development research is to develop a Powtoon-based mathematics learning media on set material. This study uses the ADDIE research method with five stages of development, namely analysis, planning, development, implementation and evaluation. However, the research was modified from 5 stages to 3 stages, namely analysis, design, and development. The subjects in this research and development were seventh grade students of SMP IT Muhammadiyah Simpang Empat, two material experts consisting of a material expert lecturer and a mathematics teacher as a validator of the feasibility of learning media, one media expert, namely a media expert lecturer. The result of this research is mathematics learning media in the form of animation video based on Powtoon. The feasibility of the media is said to be valid by material experts and media experts and gets a good response. Based on the results of data analysis, the average value obtained from material experts is 4.52 and media experts is 4.6. From these results it can be stated that the mathematics learning media meets the validity requirements of the learning media and is included in the very good category.